Analysis of the Development of Electronic Teaching Materials Integrated with Problem Based Learning to Promote Critical Thinking Skills: Systematic Literature Review - Feziyasti, Azifa; Suhengki, Michelly Fathimatuzzahra; Pratiwi, Aulianisa Dina; Asrizal, Asrizal; Festiyed, Festiyed (Universitas Negeri Padang, 2025)
This article aims to analyze the development of electronic teaching materials based on the Problem-Based Learning (PBL) model to promote student’s critical thinking skills. Ideally, education should facilitate students in thinking critically, creatively, and independently when facing various problems. However, challenges in achieving this ideal condition often arise due to the lack of effective learning models. Using the Systematic Literature Review (SLR) method, this study examines various previous studies related to develop of electronic teaching materials based on Problem Based Learning. Based on the literature analysis conducted, it was found that research on the development of electronic teaching materials using the Problem-Based Learning model has been discussed in 20 journal articles analyzed. These articles indicate that the Problem-Based model in electronic teaching materials has great potential in facilitating the improvement of critical thinking skills, especially in the context of interactive and structured learning. These findings are expected to provide insights for curriculum developers and educators in designing more effective and innovative teaching materials, as well as to encourage further research in this field